Early Cognitive Predictors of 9-Year-Old Spoken Language in Children With Mild to Severe Hearing Loss Using Hearing Aids - Ching, Teresa Y. C.; Cupples, Linda; Marnane, Vivienne (Frontiers in Psychology, 2019)
This study examined the extent to which cognitive ability at 5 years of age predicted language development from 5 to 9 years of age in a population-based sample ofc children with hearing loss who participated in the Longitudinal Outcomes of Children with Hearing Impairment (LOCHI) study. The developmental outcomes of 81 children with hearing loss were evaluated at 5 and 9 years of age. Hearing loss ranged from mild to severe degrees, and all participants used hearing aids. They all used spoken language as the primary mode of communication and education. Nine-year-old language was assessed using the Clinical Evaluation of Language Fundamentals – 4th edition (CELF-4), the Peabody Picture Vocabulary Test – 4th edition (PPVT-4) and the Expressive Vocabulary Test – 2nd edition (EVT-2). Multiple regression analyses were conducted to examine the extent to which children’s scores on these standardized assessments were predicted by their cognitive ability (nonverbal IQ and verbal working memory) measured at 5 years of age. The influence of early language scores at 5 years and a range of demographic characteristics on language scores at 9 years of age was evaluated. We found that 5-year-old digit span score was a significant predictor of receptive and expressive language, but not receptive or expressive vocabulary, at 9 years of age. Also, 5-year-old nonword repetition test score was a significant predictor of only expressive language and vocabulary, but not receptive language or vocabulary at 9 years of age. After allowing for the effects of nonverbal IQ and 5-year-old receptive vocabulary, early digit span score (but not nonword repetition score) was a significant predictor of expressive and receptive language scores at 9 years of age. The findings shed light on the unique role of early verbal working memory in predicting the development of receptive and expressive language skills and vocabulary skills in children who use hearing aids.